Aerobic microflora in the pathogenesis of maxillary sinusitis after the treatment of caries complications - Varzhapetian, S.; Makarenko, O.; Sydoryako, A.; Baleha, M.; Bunyatyan, Kh.; Варжапетян, Сурен Діасович; Сидоряко, Андрій Вікторович (My University, 2019)
Most sinusitis is the result of a periapical infection caused by caries or periodontal disease. The role of bacteria in the initiation of inflammation of the pulp and periapical zones has been well demonstrated. It is well known that colonization of microorganisms in the oral cavity can contribute to the development of pathology of the pulp and periapical organs. Purpose - to study the pathogenesis of maxillary sinusitis, which developed during the treatment of complications of caries of the upper jaw. The study involved 17 patients (mean 40.5±12.7 years) with maxillary sinusitis after treatment of complications of dental caries of the upper jaw. In 8 (47.2%) patients, the species composition of microflora in the sinuses was revealed. Material for the study was taken from the maxillary sinuses during the operative intervention. 24 hours before the operation, antibiotics were discontinued. Identification of isolated aerobic cultures and fungi was carried out using a Vitek 2-compact (BioMérieux, France). The susceptibility of antibiotics to the isolated microorganisms was determined using a Vitek 2-compact bacteriological analyzer. In 9 (53.0%) patients venous blood sampling was carried out in accordance with the recommendations of the Zaporizhzhya laboratory Synevo (Belgium) for the study of general immunity. Aerobic bacteria were sown in 100.0% of patients. Gram-positive flora - staphylococcus and streptococcus (80.0%) and fungi - candida (20.0%). Monocultures were detected in 75.0% of patients, associations - in 25.0%. The maximum bacterial contamination index is 105 CFU, detected in 20.0% of cases; the minimum figure was 103 CFU, was found in 50.0% of cases. High Ig E values (173.3±76.7 IU/ml) and low CIC values (160 OU) indicate the presence of an allergic component in the pathogenesis of the disease and an adequate immune system response to sensitization and inflammation in patients in this group.
Keywords: maxillary sinusitis; aerobic microflora; iatrogenic forms of maxillary sinusitis; differential diagnosis; classification of sinusitis